Sistem Stock Opname Berbasis Android Menggunakan Teknologi QR Code Studi Kasus : PT. Susun Arta Raharja - Nur Syifa Fauziah; Yudi Kurniawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Now a days human life certainly cannot be separated from the management of circumstances and needs, such as managing daily data needs, the need for activities that must be regulated based on the circumstances of life that occur, managing time and work and all other activities. Stock taking is a form of a series of activities for calculating the stock of goods that are still stored in the warehouse and then sent to the customer when ordering goods. There are many activities included in it, starting from counting the number of goods, conducting direct inspections so that the goods sent are not rejected, as well as making arrangements that will facilitate business operations when a certain product is needed. then the problem raised in this study is how to optimally control the inventory of goods in the warehouse by considering the product expiry rate and product returns in order to minimize the total cost of inventory. In addition, in carrying out calculations there should also be no mistakes or missed ones, because later it will affect the stock of goods being sold. Now with technological developments, there is already a QR Code (Quick Response Code) technology. By using a QR Code, the stock taking process can be done more quickly and efficiently.